PENGARUH APLIKASI FITOHORMON TERHADAP PERKECAMBAHAN BENIH GAHARU (Gyrinops versteegii) PASCA PROSES PENYIMPANAN - Sarowan Wahid; I Gde Adi Suryawan Wangiyana (Universitas Muhammadiyah Mataram, 2021)
The purpose of this research was to examine the effect of phytohormone and its concentration on germination of 1-week storage G. versteegii’s seeds. Factorial Completely Randomize Design was used with two factors: type of phytohormone (J1:Atonik, J2:gibberellic acid) and phytohormone concentration (K1:200ppm, K2:400ppm). ANOVA shows that phytohormone concentration was the only factor that has a significant difference at α=0.05. Four hundred ppm was an ideal concentration that supports G. versteegii’s seed's better germination rate on atonic and gibberellic acid. However, gibberellic acid has supported a better germination rate than atonic at 400 ppm concentration. It is concluded that gibberellic acid at 400 ppm concentration is the best treatment for G. versteegii germination.